SEJARAH PEMIKIRAN EKONOMI MERKANTILIS DAN EKONOMI KLASIK ADAM SMITH - Riema Ainun Nissa; Dwi Ayu Septiyani; Muthia Husna Qolby; Ibrahim Abdu Salam; Muhammad Taufiq Abadi; Muhammad Aris Syafi’i (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The history of economic thought gave birth to many economic thoughts by great figures, including mercantilist economic thought and the classical economic thought of Adam Smith. This research aims to explain the history of mercantilist economics, the figures of mercantilist economic thought and the classical economic history of Adam Smith. This research method is through library research in the form of journals, articles, and e-books on the history of mercantilist and classical economic thought (Adam Smith). Mercantilism theory states that the welfare of a country is only determined by the amount of assets or capital stored by the state. The main focus of Adam Smith's classical economic thought is advocating natural freedom or liberalism, self-interest, and competition. Classical economic theory is also considered the basis for the emergence of capitalist economics.